JOB FIT AND PERCEIVED SUPERVISOR SUPPORT : WHICH FACTOR HAS THE DOMINANT EFFECT ON NURSE'S INTENTION TO LEAVE? - Restantin, Riris Linda; Dewanto, Aryo (Universitas Brawijaya, 2025)
Nurse turnover negatively impacts hospital operations, which will result in cost inefficiencies and increased patient safety incidents. Studies have identified job fit (JF) and perceived supervisor support (PSS) as key factors influencing nurses’ intention to leave (NIL). This study aimed to determine whether JF or PSS has a more dominant effect on NIL in a private hospital in Malang. A quantitative cross-sectional design was used in this study, and data were collected using a 5-point Likert scale questionnaire administered to 70 nurses. A census sampling method was used. The data were then analyzed using linear regression to identify the influence of JF and PSS on NIL. The results showed that JF had a non-significant negative effect on NIL (regression coefficient of -0.226), whereas PSS had a significant negative effect (regression coefficient of -0.745). Standardized coefficient measurement indicated that PSS (-0.617) had a stronger effect on NIL compared to JF (-0.149). These results indicate that PSS is the more dominant factor influencing NIL. Hospitals should prioritize strategies related to PSS to reduce turnover by creating a supportive work environment, fostering supervisors’ ability to meet the socio-emotional needs of nurses, and implementing policies that enhance nurse performance and well-being.